Hedonism in David Frankel’s: The Devil Wears Prada - Syamsul Bahri; Intan Nia Salsabila; Joice Stefanie Ginting; Amelia Amelia (Lembaga Pengembangan Kinerja Dosen, 2025)
The film The Devil Wears Prada portrays various aspects of hedonism, especially in the pursuit of pleasure, luxury, and social status. These behaviors are increasingly visible today, especially among Generation Z and people of all ages, where the desire for immediate gratification strongly influences lifestyle and personal choices. This growing presence of hedonistic values inspires the writers to explore the concept more deeply, aiming to understand how it shapes attitudes and decisions in contemporary society. The aim is to recognize and comprehend the different forms of hedonism depicted in the film. This study employs a qualitative explanation approach to examine the attitudes, conversations, and actions of the key characters: Miranda Priestly, Andrea Sachs, and Emily Charlton. The results indicate that six categories of hedonism arise, according to Weijers’ (2012) framework: folk hedonism (25%), value/prudential hedonism (20%), motivational hedonism (18%), normative hedonism (12%), egoist hedonism (15%), and utilitarian hedonism (10%). Among them, folk hedonism is the most common, particularly in characters that pursue immediate pleasure without considering the long-term consequences. The research finds that The Devil Wears Prada illustrates how hedonism affects character growth and choices, reflecting real-life patterns where immediate gratification frequently overshadows long-term repercussions.